2015
DOI: 10.1371/journal.pone.0122602
|View full text |Cite|
|
Sign up to set email alerts
|

Binary Gene Expression Patterning of the Molt Cycle: The Case of Chitin Metabolism

Abstract: In crustaceans, like all arthropods, growth is accompanied by a molting cycle. This cycle comprises major physiological events in which mineralized chitinous structures are built and degraded. These events are in turn governed by genes whose patterns of expression are presumably linked to the molting cycle. To study these genes we performed next generation sequencing and constructed a molt-related transcriptomic library from two exoskeletal-forming tissues of the crayfish Cherax quadricarinatus, namely the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
(53 reference statements)
2
29
0
Order By: Relevance
“…In the fourth larval instar, the peaks occurred at the early stage. Similar temporal expression patterns have been documented in other insect species (Gagou et al., ; Abehsera et al., ). In Lepidopterans, BmChSA transcription in B. mori was upregulated in the premolting process through the end of ecdysis, in contrast to that at the mid instar stage (Zhuo et al., ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the fourth larval instar, the peaks occurred at the early stage. Similar temporal expression patterns have been documented in other insect species (Gagou et al., ; Abehsera et al., ). In Lepidopterans, BmChSA transcription in B. mori was upregulated in the premolting process through the end of ecdysis, in contrast to that at the mid instar stage (Zhuo et al., ).…”
Section: Discussionsupporting
confidence: 83%
“…In Diptera insects, DmChSA and DmChSB expression in D. melanogaster was upregulated in a stage‐specific manner during the onset of metamorphosis (Gagou et al., ). In Crustacea Cherax quadricarinatus , ChS in the gastrolith‐forming epithelium was highly expressed during the pre‐ and postmolting stages (Abehsera et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we identified proteins expressed in the postmoult phase of crustaceans and involved in deposition and calcification of the newly formed exoskeleton: postmoult protein ( PMP ), calcification‐associated peptide ( CaAP ), peptides DD5 and M28 (Ikeya, Persson, Kono, & Watanabe, ; Inoue, ; Roer et al., ). Among the downregulated transcripts, the majority were identified as chitinase enzymes (Abehsera et al., ) and a downregulation of a vitellogenin transcript was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of these genes is inevitably related to the phases of the moult cycle (e.g. see Abehsera et al., ; Tom et al., ). The increased expression of cuticular contigs after 7‐day exposure suggested that cyclic hypoxia might exert an effect on the moult cycle of P. varians , similarly to that reported for insect larvae reared in hypoxia (Kivelä et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another expected consequence is high variability of the overall gene expression within a stage, meaning that different individuals sampled from the same stage could have an entirely different overall gene expression pattern depending on their instar age. In crustaceans, transcriptome analysis of the adult moult cycle has been examined recently (Abehsera et al., ; Huang et al., ; Seear et al., ). In these studies, the developmental status of individuals within the moulting cycle was assigned by classifying the animals morphologically by Drach's moult staging system (Drach, ), which has also been implemented for krill (Buchholz, ).…”
Section: Introductionmentioning
confidence: 99%